Парусиновый портфель: [повести и рассказы] / Михаил Зощенко - Зощенко Михаил Михайлович (Дом, 1994)
Экземпляры: Аб (20140801) / Инвентарный номер: 101338 / Цена: 40.00 / Авт.знак: З-88 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6